Analisa Faktor Kesulitan Belajar Siswa pada Pelajaran Ekonomi dalam Kurikulum Merdeka Kelas 10 MA Darul Huda Wonodadi Blitar - Elha Fawwa Dzakira Muis (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Independent Curriculum is a curriculum implemented by the government as a new guideline for education in Indonesia. With the various curricula in Indonesia, all elements in educational institutions must be able to adjust to them. This is what can cause learning difficulties, especially for students. The objectives of this study are: 1. To find out the learning difficulties experienced by students, 2. To find out the factors that cause students' learning difficulties, 3. To find out solutions to overcome students' learning difficulties. In this study, the researcher used a qualitative method to find out the results of an in-depth analysis of the resource persons. Learning problems faced by students in the Economics lesson of the Independent Curriculum for class 10 MA Darul Huda were found, namely: 1) Attention, 2) Memory, 3) The level of students' absorption in understanding information, 4) Academic and 5) Social. Then the factors that cause students to experience difficulties in the Economics lesson of the Independent Curriculum for class 10 MA Darul Huda are Internal Factors, namely: a) Psychology and Mental and b) Emotional and Bad Attitude Habits. Then in External Factors there are: a) Family, b) School, and c) Community, So that solutions are obtained to overcome student learning problems, namely: 1. Counseling Guidance 2. Establishing Cooperation with Parents of Students 3. Principal's assessment of teachers 4. Teacher assessment of students.